Fracture severity dependence of bone and muscle performance in patients following single or multiple vertebral fractures - Zhang, Chenggui; Li, Yang; Wang, Guodong; Sun, Jianmin (Frontiers in Endocrinology, 2024)
Background: Few studies foucs on the clinical, laboratory, radiological, and biological characteristics of bone and muscle of multiple vertebral fractures, which are associated with a more poor prognosis compared with single fracture.To compare the BMD, bone turnover, muscularity, fatty infiltration of muscle, and prevalence of co-morbidities in patients with single and multiple vertebral fractures.We recruited 100 patients with single fracture (age 66.96±8.24 years) and 100 with multiple fractures (age 69.90±7.80 years); performed dual-energy X-ray absorptiometry of the femoral neck, hip, and lumbar vertebrae; and measured biochemical markers of bone turnover, muscularity, and fatty infiltration.Results: Patients with multiple vertebral fractures had lower hip BMD (p=0.010) than those with single fractures, but there was no difference in femoral neck and lumbar vertebral BMD nor in muscularity. However, fatty infiltration, an indicator of muscle quality, was significantly higher in participants with multiple fractures (p=0.006).Diabetes was significantly more common in patients with multiple fractures (p=0.042). There were no significant differences in markers of bone turnover, and Seperman analyses showed no correlations of CTX-1 or tPINP with the BMD of the hip, femoral neck, or lumbar spine. However, high CTX-1 was associated with high tPINP (r=0.4805; p<0.0001), and marked fatty infiltration was associated with low hip, lumbar vertebral, and femoral neck BMD. Cox regression analyses showed that age (OR 1.057; 95% CI 1.016-1.101; p=0.006) and low hip BMD (OR 0.016; 95% CI, 0.000-0.549; p=0.022) were associated with a higher risk of multiple fractures.Patients with multiple fractures tend to have lower hip BMD, a history of type 2 diabetes, and more substantial fatty infiltration of muscle than in those with single fractures. Age and hip BMD rather than lumbar vertebrae BMD were found to be independent risk factors for multiple vertebral compression fractures, implying that hip BMD may be a more sensitive predictor for multiple vetebral fractures. More improvements in hip BMD and focus on older persons may be useful means of preventing multiple fractures.